Analisis Faktor yang Mempengaruhi Produksi Padi Sawah di Desa Sebulu Ilir Kecamatan Sebulu Kabupaten Kutai Kartanegara - Eka Rahmawati; Agung Enggal Nugroho; Al Defri (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
The purpose of this study was to determine (i) the effect of labor, land area, fertilizer and seeds simultaneously or partially on the production of lowland rice in Sebulu Ilir Village Sebulu District, (ii) the factors of production which had the most significant influence on paddy production and (iii) ) problems of rice farmers in Sebulu Ilir Village. The study was conducted in December 2018. Using a random sampling method with a sample of 32 lowland rice farmers. Multiple linear regression analysis and classical assumption tests are used to answer the research objectives. The results showed the factors of labor production, land area, and NPK fertilizer simultaneously (together) had a positive and significant effect on lowland rice. Partially or individually the factors of labor production and land area affect the production of lowland rice while the NPK fertilizer production factor does not affect the production of lowland rice. The most influential factor on lowland rice production is labor (X1) because it has a coefficient value of 0.699 with a calculated T value of 2.408 and a significance value of 0.023. The problems faced by rice farmers in Sebulu Ilir Village are irrigation which has not been well organized, lack of counseling, lack of government assistance, and land in other village areas.